The Role of the Administration and the National Assembly in the Protection of Classified Information - Martinović, Aleksandar (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
Abstract: certain informations cannot and must not be available to the general public because they represent information of importance for national security or their publication could lead to great damage or endangerment of persons, property and other relations. In our legal system, such information is defined as secret data, which is further categorized into several groups based on its importance and the damage that may occur as a result of its publication. The protection of such data, by determining that they are secret, and carefully controlling who and how they give access to that data, is carried out by competent authorities in accordance with the law. The matter of defining secret data, use and protection of secret data in the Republic of Serbia is codified by the Data Secrecy Act, but other regulations are also applied in specific areas, which makes the entire positive legal framework for the protection of secret data extremely extensive. In the paper, the author analyzes the current legal framework and especially emphasizes the role played by the administrative bodies and the National Assembly of the Republic of Serbia in the protection of secret data.